A rewriting system for convex optimization problems. Issue 1 (2nd January 2018) - Agrawal, Akshay; Verschueren, Robin; Diamond, Steven; Boyd, Stephen
Abstract : We describe a modular rewriting system for translating optimization problems written in a domain-specific language (DSL) to forms compatible with low-level solver interfaces. Translation is facilitated by reductions, which accept a category of problems and transform instances of that category to equivalent instances of another category. Our system proceeds in two key phases: analysis, in which we attempt to find a suitable solver for a supplied problem, and canonicalization, in which we rewrite the problem in the selected solver's standard form. We implement the described system in version 1.0 of CVXPY, a DSL for mathematical and especially convex optimization. By treating reductions as first-class objects, our method makes it easy to match problems to solvers well-suited for them and to support solvers with a wide variety of standard forms.